Short-term efficiency of plasma exchange in combination with immunosuppressants and/or biologics in the treatment of idiopathic inflammatory myopathy with rapidly progressive interstitial lung disease: a systematic review and meta-analysis - Yang, Yang; Yang, Yan-Ting; Huo, Rong-Xiu; Meng, Dan-Li; Huang, Xin-Xiang; Lin, Jin-Ying (Annals of medicine (Helsinki), 2024)
Rapidly progressive interstitial lung disease (RP-ILD) is a frequent and serious manifestation of idiopathic inflammatory myopathy (IIM) associated with poor outcomes. Plasma exchange (PE) can quickly remove pathogenic substances from the blood. Therefore, PE may be efficacious in IIM patients who have elevated levels of autoantibodies, cytokines and chemokines, fighting for time for immunosuppressive therapy. However, the value of adding PE to immunosuppressants remains unclear. The purpose of this study was to determine the short-term outcomes, including the survival rate at 6 months and change of the laboratory data, of PE in combination with immunosuppressants and/or biologics in the treatment of IIM-RP-ILD. We searched PubMed, Embase and Cochrane Library to find reports of interest published from inception to March 4, 2024. STATA 15.1 was used for data analysis. A fixed or random-effects model with inverse-variance weighting was used to estimate the pooled risk ratio (RR) and 95% confidence interval (CI). Two hundred and thirty studies were identified. Eleven studies, including five retrospective cohort studies, four case-control studies and two case series, were included. PE was performed on 114 patients. The survival rate at 6 months was 80% (95%CI = 64%-92%), with moderate heterogeneity ( =63.45%, < 0.05). Moreover, the 6-month survival rate was significantly better in the PE group than in the non-PE group (RR, 1.34; 95% CI = 1.05-1.71, =30.7%; = 0.194). ILD-related serum markers, including ferritin, KL-6 and anti-MDA-5 antibody titres, were significantly suppressed by a series of PE treatments ( < 0.05). The application of PE therapy plus treatment with corticosteroids, immunosuppressants and/or biologics was effective for patients with IIM-RP-ILD. PE may have additional supportive effect in intractable disease.